2015
DOI: 10.1177/0021934715573386
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Influence of Ethnic Identity and Parental Attachment on the Body Esteem of Black Sorority Women

Abstract: The primary goal of the current study was to explore the influence of ethnic identification and parental attachment on the body esteem of Black women who were members of a Black sorority. To date, there has been no published research examining determinants of body image in this population of Black women. The authors hypothesized that ethnic identity and attachment to mother would predict body esteem in this population. One hundred twelve women (M age 39.3) were surveyed, and hierarchical regression analysis re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Sorority membership for Black women appears to be a significant component of cultural identity (Patton, Bridges, & Flowers, 2011) and a major support system (Gasman & Payton-Stewart, 2006), yet little is known about its relationship to body image. Some previous research (Baugh & Barnes, 2015) has examined body image in Black sorority women, but the literature is lacking on this group and their experiences. Therefore, the aim of this paper is to add to the literature on the body image of Black sorority women through a comparison study to nonsorority women.…”
Section: Eboni J Baugh East Carolina Universitymentioning
confidence: 99%
“…Sorority membership for Black women appears to be a significant component of cultural identity (Patton, Bridges, & Flowers, 2011) and a major support system (Gasman & Payton-Stewart, 2006), yet little is known about its relationship to body image. Some previous research (Baugh & Barnes, 2015) has examined body image in Black sorority women, but the literature is lacking on this group and their experiences. Therefore, the aim of this paper is to add to the literature on the body image of Black sorority women through a comparison study to nonsorority women.…”
Section: Eboni J Baugh East Carolina Universitymentioning
confidence: 99%
“…Because certain research has also indicated that ethnic identity acts as a protective factor against thin ideals, this could further compound the effect. As previously stated, African-American women tend to feel more strongly attached to their ethnic identity than women from other ethnic groups; 11,12 however, it is unclear to what degree this attachment is positively or negatively associated with motivation for engaging in a healthy lifestyle. Understanding the unique impact of identity and its relation to engagement in health behaviors is crucial in a population that experiences some of the worst health outcomes in a variety of areas, such as rates of obesity and diabetes.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, African-American women tend to feel more strongly attached to their ethnic identity than European American women. 11,12 The level of identification with one's ethnicity can impact multiple facets of life, especially if one strongly identifies with their ethnicity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations